Selection of the best secondary school student using the CRITIC-PROMETHEE II method / Ahmad Qawiem Jamalludin, Ahmad Zulhakim Azhar and Zulaikha Husna Khairul Anuar - Jamalludin, Ahmad Qawiem; Azhar, Ahmad Zulhakim; Khairul Anuar, Zulaikha Husna (2023)
School is an institution or an effective place to transforms knowledge from educators to students and as a means of education. Students learn more information and develop their morals here. In order to inspire each student's excitement for improving the learning process, the best students are chosen over a certain period of time. The selection of the best secondary school student is one of the decision-making problems that can be solved using Multi-Criteria Decision Making (MCDM) method. However, determining criteria weights is a problem faced by many MCDM methods. Therefore, the objectives of this study are to integrate the Criteria Importance Through Intercriteria Correlation (CRITIC) method with the Preference Ranking Organisation Method for Enrichment Evaluations (PROMETHEE) II method in solving the best student selection problem, to rank the secondary school students using the CRITIC-PROMETHEE II method and to perform the sensitivity analysis over the CRITIC-PROMETHEE II method in measuring the consistency of the student ranking in various conditions. A real-life data about the best secondary school student selection for SPM 2021 examination is implemented to demonstrate the application of the CRITIC-PROMETHEE II method.